Estudo da produção de nanofibras de carbono por fiação por sopro em solução a partir de poliacrilonitrila e lignina - Camargo, Lais Angelice de (2019)
Carbon nanofibers (NFC) are highly resistant materials and are widely used in the aerospace and battery industry. Methods such as eletrospinning and solution blow spinning (SBS) are used for the production of carbon nanofibers and these can be produced from polyacrylonitrile (PAN), among other petroleum polymers. In this work the carbon nanofiber production by SBS from PAN enriched with lignin content from bio-residue was studied. The nanofibers produced in this work were characterized by physicochemical properties by XRD, FTIR, Raman and NMR, thermal properties by Thermogravimetry (TG/DTG) and Differential Exploratory Calorimetry (DSC), as well as structural properties by Microscopy Scanning Electronics (SEM). An experimental design was carried out to optimize the nanofiber production parameters of PAN by SBS and those that influenced the nanofiber diameter according to the model were PAN concentration and the injection rate, thus, the higher the concentration and the lower the injection rate, the larger the nanofiber diameters. NFC from PAN were produced by SBS and presented an average diameter of 153.2 nm for 6 %, 254.0 nm for 8 % and 369.0 nm for 10 % of mass fraction confirming the tendency of concentration increase with increased diameter of the produced nanofibers indicated by experimental design. Carbon nanofibers from PAN with the addition of lignin were obtained up to the 20:80 PAN/Lignin fraction for 18 % mass concentration. For the ratio of 10:90 PAN/Lignin it was only possible to obtain nanofibers from the fixed viscosity of the 0.2 Pa.s solution for both wood lignin (Lig-M) and sugar cane lignin (Lig-C). These nanofibers had an average diameter of 228.5 and 300.6 nm, R (ID/IG) of 1.26 and 1.22 and crystal size of 15.3 and 15.7 nm respectively. These results for carbon nanofibers obtained through Lig-M and Lig-C by SBS corroborate those found in the literature for nanofibers produced from eletrospinning. Thus carbon nanofibers with up to 90% lignin were successfully produced in this work using the new solution blow spinning technique.